External Limiting Membrane Disruption Predicts Long-Term Outcome in Strict Treat-And-Extend Regimen in Neovascular Age-Related Macular Degeneration - Hoffmann, Laura; Hatz, Katja (Frontiers in Medicine, 2021)
The use of anti-vascular-endothelial growth factor agents for neovascular age-related macular degeneration (nAMD) in different treatment schemes is widely common in clinical practice. However, there is currently limited data on the long-term outcomes of a strict treat-and-extend regimen (TER) and imaging biomarkers to predict both functional outcome and the potential for a TER exit due to success. In this retrospective study we followed treatment-naïve subjects with nAMD starting treatment with either ranibizumab or aflibercept in a TER without loading dose but with predefined exit criteria for up to 8 years. We evaluated both the functional outcome and several spectral-domain optical coherence tomography parameters in a follow-up mode using a standardized protocol. Within the 211 eyes followed for a mean of 60.3 ± 20.9 months, follow-up adherence was high with major part of discontinuations of TER being due to success. Mean best-corrected visual acuity (BCVA) increased from initially 63.9 ± 15.5 ETDRS letters to 70.0 ± 14.7 after 1 year (+6.1 letters, p < 0.001) and to 68.5 ± 18.1 (+4.6 letters, p = 0.028) at 5 years. A worse BCVA (p = 0.001) and a better external limiting membrane (ELM) disruption score at baseline predicted (p = 0.019) BCVA gain at 5 years. The probability of reaching the exit criteria was significantly associated with a better ELM disruption score (p = 0.044) and the absence of a central pigment epithelial detachment (PED) (p = 0.05) at baseline. Significant visual gains were sustained in a long-term TER in a real-world setting. Integrity of ELM at baseline predicted BCVA gain at 5 years and the potential for TER exit due to success.